Technology Readiness Index (TRI) Pengguna Kompor Induksi di Indonesia (Studi Kasus: Pilot Project Konversi Kompor Gas LPG ke Kompor Induksi di Surakarta) - Rizky, Dania Latifa; Damayanti, Retno Wulan; Laksono, Pringgo Widyo (Jurnal Sosioteknologi, 2025)
To reduce dependency on LPG imports, the Indonesian government, through PT PLN (Persero), is implementing a project to convert LPG gas stoves to induction stoves, utilizing the national electricity surplus and reducing the energy subsidy burden. This study measures the technology readiness level of induction stove users in Surakarta, specifically the Beneficiary Families (KPM), using the technology readiness index (TRI). The results show that the KPM's TRI value is 3.33, which falls into the moderate category, indicating that the KPMs are considered pioneers ready to adopt this technology. However, there are still concerns about the technology's performance not meeting their expectations. The academic contribution of this study lies in developing an understanding of the adoption of induction stove technology in Indonesia, particularly the technology readiness within the community. The practical implications suggest the need for communication and training strategies to alleviate users' anxieties. From a social, economic, and environmental perspective, stakeholders need to formulate policies that support this transition by considering energy sustainability, reducing dependence on fossil fuels, and improving community welfare.